1993
DOI: 10.1103/physreve.48.1787
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear hydrodynamics of a hard-sphere fluid near the glass transition

Abstract: We conduct a numerical study of the dynamic behavior of a dense hard sphere fluid by deriving and integrating a set of Langevin equations. The statics of the system is described by a free energy functional of the Ramakrishnan-Yussouff form. We find that the system exhibits glassy behavior as evidenced through stretched exponential decay and two-stage relaxation of the density correlation function. The characteristic times grow with increasing density according to the Vogel-Fulcher law. The wavenumber dependenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…The other runs yielded only lower bounds τ 1 > 120,000 MCS, that is, the system remained in the domain of attraction of the initial minimum. We did not need to calculate τ 1 for n * ≤ 0.93 because our previous studies 17,18 showed that for such densities, a system initially prepared in the liquid state, remains in the vicinity of the uniform liquid minimum for all time scales accessible in our Langevin simulations. We see from Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The other runs yielded only lower bounds τ 1 > 120,000 MCS, that is, the system remained in the domain of attraction of the initial minimum. We did not need to calculate τ 1 for n * ≤ 0.93 because our previous studies 17,18 showed that for such densities, a system initially prepared in the liquid state, remains in the vicinity of the uniform liquid minimum for all time scales accessible in our Langevin simulations. We see from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, [17][18][19][20] we have studied the dynamical properties of this model by introducing the appropriate Langevin dynamics. Briefly, one introduces the additional current field g(r) and the total free energy:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations